Integrated Farming System for Sustainable Income: Success Story of an Innovative Farmer - Pallavi, Ch.; Sridevi, S.; Vijay, J.; Swetha, D.; Saritha, A.; Umarani, E.; Srijaya, T.; Ramadevi, A. (Chronicle of Bioresource Management, 2024)
In Siddipet district, paddy is the predominant crop, occupying 72% of the total cropped area. However, paddy cultivation is highly input and labor-intensive, yielding lower net profits ranging from Rs. 25,000 to Rs. 50,000 ha-1. To address these challenges, the Agricultural Research Station (ARS) and District Agricultural Advisory and Transfer of Technology Centre (DAATTC), Tornala, introduced an Integrated Farming System (IFS) in 2020. IFS is a sustainable agricultural practice that combines livestock, crop production, fishery, poultry, tree crops, plantation crops, etc., to create mutually beneficial relationships. The goal is to enhance productivity and profitability for marginal farmers through the IFS approach, which is based on the principle that “waste is only a misplaced resource,” meaning that waste from one component of the system can serve as an input for another rather than relying solely on paddy cultivation. This success story highlights an inspiring example of a farmer who has effectively implemented IFS in Siddipet district, Telangana.